A new Carboniferous–Permian intra‐oceanic subduction system in the North Tianshan (NW China): Implications for multiple accretionary tectonics of the southern Altaids. (17th February 2020) - Bai, Xueyin; Chen, Yichao; Song, Dongfang; Xiao, Wenjiao; Windley, Brian F.; Ao, Songjian; Li, Liang; Xiang, Dunfeng
Abstract : The North Tianshan in NW China is a key to understanding the accretionary history of the southern Altaids. However, the tectonic setting of the North Tianshan in the Carboniferous‐Permian is debatable, and its amalgamation history is ambiguous. We report new data on the field relations, geochronology and geochemistry of Carboniferous–Jurassic volcanic rocks and sedimentary rocks from the Shichang area in order to constrain the late Palaeozoic–Early Mesozoic tectonic evolution of the North Tianshan. New LA‐ICP‐MS zircon U–Pb dates demonstrate that the Carboniferous–Permian stratigraphy is a tectonic imbrication of Carboniferous–Permian rocks and Carboniferous volcanic rocks were emplaced in Permian volcano‐sedimentary rocks. The 311 ± 2 Ma volcanic rocks are calc‐alkaline, enriched in Light Rare Earth Elements and large‐ion lithophile elements, depleted in high‐field‐strength elements, and have low initial 87 Sr/ 86 Sr ratios with positive ε Nd ( t )(+0.3 to +8.6)values. The geochemical‐isotopic data suggest the volcanic rocks were generated in an intra‐oceanic island arc. The turbidite samples 18SC02 (~267 Ma to ~349 Ma) and 18SC09 (~299 Ma to ~369 Ma) have a relatively narrow age range with no Devonian or Precambrian peaks. Our detrital zircon data suggest the presence of a so far unrecognized intra‐oceanic arc, which was isolated from the main Yili‐Central Tianshan and Mosuowan arcs in the Shichang area of the North Tianshan during the Late Carboniferous to Permian. The compiled detrital zircon data from Carboniferous to Jurassic indicates that the North Tianshan intra‐oceanic arc was probably amalgamated with the Mosuowan arc by the Early Triassic, and then accreted to the Yili‐Central Tianshan arc by the Middle‐Late Triassic, as revealed by the changes of zircon provenance of Carboniferous, Permian, Triassic and Jurassic sedimentary rocks. All integrated data suggest that the southern Altaids most likely formed by processes of multiple subduction–accretion and convergence similar to that in the ongoing southwest Pacific.